HUBUNGAN PELAYANAN INFORMASI OBAT DENGAN TINGKAT KEPATUHAN PASIEN DALAM PENGOBATAN HIPERTENSI DI PUSKESMAS KEDIRI LOMBOK BARAT - En Purmafitriah; Evi Fatmi Utami; Anisa Utami (LPPM Universitas Awal Bros, 2026)
Hypertension is one of the chronic diseases with a high prevalence in Indonesia and often leads to serious complications if not properly managed. Patient adherence to hypertension therapy plays a crucial role in achieving optimal treatment outcomes. This study aims to determine the relationship between drug information services and the level of adherence among hypertensive patients at Kediri Public Health Center, West Lombok. This research is a non-experimental quantitative study with a descriptive correlational design using a prospective approach. The sample consisted of 100 hypertensive patients selected through purposive sampling. The results showed that the majority of patients (80%) were adherent to medication, 12% were less adherent, and 8% were non-adherent. The statistical test used in this study was a correlation test with the assistance of SPSS. The statistical analysis indicated a significant relationship between drug information services and the level of adherence among hypertensive patients, with a significance value of 0.042. In conclusion, there is a relationship between drug information services and the level of adherence among hypertensive patients, with a moderate degree of correlation. The better the drug information services provided, the higher the level of patient adherence in hypertension treatment.